Assessment of Lifestyle and Risk Behaviour Practices among Undergraduate Medical Students - Jain, Manish; Jain, Mayank; Kumar, Vinod; Garg, Kapil; Qurishi, Asif Ahmed; Gupta, Pankaj Kumar (National Journal of Community Medicine, 2019)
Introduction: Medical students are future physicians. Life style and risk behaviour practices that are acquired in early life and in medi- cal college will have a direct impact on their clinical performances. Objective: to assess the dietary habits, physical activity and current habits of smoking, smokeless tobacco uses and alcohol consump- tion among undergraduate medical students. Material and method: A pretested, self-administered questionnaire was used for collection of data regarding socio-demographic char- acters i.e. age, sex, residence, and lifestyle ie. dietary habits, physical activities and risk behaviour practices i.e. smoking, smokeless to- bacco use and alcohol consumption. Results: 59.4% students had breakfast daily. Daily consumption of at least 5 portions fruits and vegetables was reported by only 36.9% of students. Moderate physical activity for at least 30 min/day for 5 or more days was reported by only 23.6% students. 15.6% students had junk foods 4-5 times a week while 29.7% had 2-3 times a week. Habits of smoking and alcohol consumption were significantly higher among male undergraduate students. Conclusion: The study revealed poor dietary habits, inadequate physical activity and high prevalence of substance abuse among the medical students. The students should be motivated to adopt healthy life style practices.